The Relationship of Marketing Mix With Patient Loyalty At Inpatient Unit Of Undata General Hospital - Hapsa, Hapsa (Tadulako University, 2019)
Hospital is an individual health care institution plenary, bused on continuous improvement in service quality and active marketing management. The marketing mix consists of 7P namely product, price, place, promotion, people, process, and physical evidence. The (RSUD) Undata Central Sulawesi Province is a referral hospital where the number of general patient visits in the inpatient unit has decreased over the past 3 years, indicating a decrease in patient loyalty. This study aims to determine the relationship of marketing mix with patient loyalty in the inpatient unit of the regional general hospital (RSUD) Undata Central Sulawesi Province. The research method used is quantitative with a cross sectional approach. The population is all inpatients of the undata general hospital which number 1.255 sampling technique was proportional stratified sampling. Data analysis used in this study is univariate and bivariate analysis with a value of p≤0,05. The results show that there is a marketing mix relationship product (p=0,000), price (p=0,002), place (p=0,001), promotion (p=0,000), people (p=0,000), process (p=0,000), and physical evidence (p=0,018) with patient loyalty in the inpatient unit of the regional general hospital undata in palu. It is expected that the (RSUD) Undata Palu will further improve the quality of its marketing mix in SDM professionalisme, service speed, physical quality, and hospital equipment.